Pengaruh Brand Image dan Harga Terhadap Keputusan Pembelian Cold Presed Juice Merek Rejuve - Ratnasari; Vina Meliana (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
This study aims to determine the effect of brand image and price on purchasing decision of Re.juve brand cold presed juice. This study uses quantitative method with purposive sampling data collection techniques, respondents in this study there are 155 respondents with a population of people who know the products of Re.juve. The results of this study that brand image affects purchasing decisions, price determines purchasing decisions, brand image and price together influence purchasing decisions.